Qfd Based Modelling for E-Business: A Sustainable Approach using Blended Value Dimensions - Dewan, Mohammed Naim Ahmed; Chowdhury Md. Maruf Hossan; Quaddus, Mohammed (PACIS, 2012)
Business modelling is not new and has had substantial impacts on the way businesses are planned and operated these days. Although ‘e-business’ and ‘sustainability’ are the two current major global trends but surprisingly none of the e-business modelling ideas covers the sustainability aspects of the business. Researchers are introducing ‘green IT/ICT’ concept lately but none of them clearly explains how those concepts will be used by the e-business modelling ideas. Recently, companies are successfully using QFD as a powerful tool in various fields that addresses strategic and operational decisions in businesses. This research approach, therefore, develops a QFD based e-business model in conjunction with blended value and sustainability aspects. The model explores and determines the optimal design requirements in developing the model. This approach also demonstrates how the sustainability dimensions can be integrated with the value dimensions in developing an e-business model. This approach is unique in the sense that in developing the model sustainability concept is integrated with customer’s value requirements, business’s value requirements, and process’s value requirements instead of only customer’s requirements. QFD, AHP, and Delphi method are used for the analysis of the data. An illustration is provided for the enhanced understanding of the proposed approach.